Relationship Perception of Parenting and Peer Social Support with Prosocial Behavior - Siti Wulandari; Marjohan Marhojan; Riska Ahmad (International Journal of Research in Counseling and Education, 2018)
Decreasing prosocial behavior shown bystudents is one of the problems associated with perceptions of parenting and peer social support. The purpose of this study was to reveal the relationship between perceptions of parenting and peer social support,and prosocial behavior. This study uses a correlational method and data was collected from a sample of 239 students, who were found using a purposive sampling technique. Data was collected using a scale of perception on parenting (37 valid items,α = 0.944), peer social support scale (31 valid items,α = 0.934) and prosocial behavior scale (45 valid items,α = 0.935). Data were then analyzed by multiple regression. The results show a correlation coefficient r = 0.173 and p = 0.00 (p> 0.05), which shows that there is a positive and significant relationship between perceptions of parenting and peer social support together with prosocial behavior.